2007
DOI: 10.1101/lm.488707
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and the spacing effect: Learning over time enhances memory and the survival of new neurons

Abstract: Information that is spaced over time is better remembered than the same amount of information massed together. This phenomenon, known as the spacing effect, was explored with respect to its effect on learning and neurogenesis in the adult dentate gyrus of the hippocampal formation. Because the cells are generated over time and because learning enhances their survival, we hypothesized that training with spaced trials would rescue more new neurons from death than the same number of massed trials. In the first ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(129 citation statements)
references
References 42 publications
13
112
0
4
Order By: Relevance
“…As previously reported in rats, our results indicate that spatial learning also promoted long-term survival of newborn neurons in the DG of mice (12)(13)(14)24). At the time of remote memory retrieval, assessed by a probe test given 30 days after acquisition, we found that a small but significant number of new neurons were activated, thereby revealing their functional contribution to relevant hippocampal assemblies that enable spatial navigation to the hidden goal.…”
Section: Discussionsupporting
confidence: 67%
“…As previously reported in rats, our results indicate that spatial learning also promoted long-term survival of newborn neurons in the DG of mice (12)(13)(14)24). At the time of remote memory retrieval, assessed by a probe test given 30 days after acquisition, we found that a small but significant number of new neurons were activated, thereby revealing their functional contribution to relevant hippocampal assemblies that enable spatial navigation to the hidden goal.…”
Section: Discussionsupporting
confidence: 67%
“…Nearly 80% of the cells labeled with BrdU also expressed the immature neuronal marker doublecortin (DCX) (16). The percentage of BrdU-labeled cells that coexpressed DCX was similar in males and females, as reported previously (19).…”
Section: Fig 2 Learning Increased the Survival Of New Cells In The supporting
confidence: 58%
“…Secondary antibodies were Rhodamine Red-X anti-goat (Jackson Immunoresearch) and Fluro 488 antimouse (Molecular Probes). The number of cells that expressed both markers was determined using a confocal laser scanning microscope (16). Twenty cells per subject (n ϭ 4) were counted on random sections throughout the hippocampus (See SI Methods for details).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations